Effect of Lateral Sliding Calcaneus Osteotomy on Tarsal Tunnel Pressure. Issue 3 (14th August 2020) - Halm, Sebastian; Fairhurst, Paul G.; Tschanz, Stefan; Wieland, Fluri A. M.; Djonov, Valentin; Krause, Fabian
Background: Lateral sliding calcaneus osteotomies are common procedures to correct hindfoot varus deformities. Shifting the calcaneal tuberosity laterally (lateralization) can lead to tarsal tunnel pressure increase and tibial nerve palsy. The purpose of this cadaveric biomechanical study was to investigate the correlation of lateralization and pressure increase underneath the flexor retinaculum. Methods: The pressure in the tarsal tunnel of 12 Thiel-fixated human cadaveric lower legs was measured in different foot positions and varying degrees of calcaneal lateralization. Results: The mean pressure increased from plantarflexion (PF) to neutral position (NP) and from NP to hindfoot dorsiflexion (DF), and with increasing amounts of lateralization of the calcaneal tuberosity. The mean baseline pressure in PF was 1.5, in NP 2.2, and in DF 6.5 mmHg and increased to 8.1 in PF, 18.4 in NP, and 33.1 mmHg with 12 mm of lateralization. The release of the flexor retinaculum significantly lowered the pressure. Conclusion: Increasing pressures were found in the tarsal tunnel with increasing lateralization of the tuberosity and with both dorsiflexion and plantarflexion of the ankle. Clinical Relevance: A pre-emptive release of the flexor retinaculum for a lateralization of the calcaneal tuberosity of more than 8 mm should be considered, especially if specific patient risk factors are present. No tibial nerve palsy should be expected with 4 mm of lateralization.